Social Media and Development in a Hybrid Intentional Community in Rural Hong Kong - Davison, Robert M. (International Journal of Knowledge Content Development & Technology, 2025)
I explore how social media applications are applied by members of a hybrid, intentional eco-community in rural Hong Kong. I draw on both my own participant observations over the year I spent in the community and interview data with ten of the community’s members to construct an ethnographic account of social media use in the community. Social media apps are ubiquitous, yet their effects are not entirely positive. Although the technological affordances enable both the community and its members to grow, a darker side is also revealed, where increasing levels of individualism interfere with the community-level ethos and potentially threaten the community’s long-term survival. The practical and theoretical contributions of the study are discussed.